1982
DOI: 10.1002/jcb.240200104
|View full text |Cite
|
Sign up to set email alerts
|

Insulin binding sites on the nuclear envelope: potential relationship to mRNA metabolism

Abstract: Insulin regulates the growth and metabolism of most tissues. The hormonal potency of insulin results, to a large extent, from its ability to regulate target cells at a variety of subcellular sites. For many years, the effects of insulin on membrane transport, enzyme activity, and protein synthesis have been studied extensively. Less attention, however, was given to how insulin regulates nuclear functions. Recently the presence of specific binding sites for insulin on nuclei and nuclear envelopes have been docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The previously observed inhibition of pituitary GH mRNA levels induced by IGF-I (10) may have been due to other posttranscriptional events, including an increase in GH mRNA degradation, processing, or transport (34). The half-life of GH mRNA in GH cells has been reported to range from 40 to 56 h (30), while in other studies a shorter half-life has been reported (31).…”
Section: Methodsmentioning
confidence: 91%
“…The previously observed inhibition of pituitary GH mRNA levels induced by IGF-I (10) may have been due to other posttranscriptional events, including an increase in GH mRNA degradation, processing, or transport (34). The half-life of GH mRNA in GH cells has been reported to range from 40 to 56 h (30), while in other studies a shorter half-life has been reported (31).…”
Section: Methodsmentioning
confidence: 91%
“…More controversially, studies going back several decades have suggested that IR are found in cell nuclei (Goldfine et al, 1982; Podlecki et al, 1987; Smith et al, 1997). There is also evidence for insulin/IGF-1 induced nuclear localization of IRSs (Sun et al, 2003; Wu et al, 2003; Chen et al, 2005).…”
Section: Receptor Traffickingmentioning
confidence: 99%
“…Similarly, intracellular insulin can stimulate nuclear membrane receptors and result in the generation of second messengers. 17,28 Intracellular angiotensin II has also been shown to interact with intracellular receptors and generate second messengers. 34,35 These observations suggest that in some cases, the intracellular action of a hormone can modulate or amplify a signal at the cell surface, because the intracellular hormone is seen to release the same (or similar) second messengers as binding of hormone to cell-surface receptors.…”
mentioning
confidence: 99%
“…sengers, eg, insulin 17,27,28 ; (4) binding to nucleolar components, eg, FGF, PTHrP, angiogenin 13,18,20 ; and (5) binding to chromatin, eg, angiotensin II, PTHrP, nerve growth factor (NGF), EGF, and PDGF. 3,12,18,21,29 Given these observations, it appears important to determine the actions of intracellular hormones, whether they are synthesized intracellularly or internalized.…”
mentioning
confidence: 99%